Triple-channel microreactor for biphasic gas–liquid reactions: Photosensitized oxygenations - Maurya, Ram Awatar; Park, Chan Pil; Kim, Dong-Pyo (Beilstein Journal of Organic Chemistry, 2011)
A triple-channel microreactor fabricated by means of a soft-lithography technique was devised for efficient biphasic gas–liquid reactions. The excellent performance of the microreactor was demonstrated by carrying out photosensitized oxygenations of α-terpinene, citronellol, and allyl alcohols.
Keywords: gas–liquid reaction; microreactor; photosensitization; singlet oxygen